Helical flow during rotational pipe extrusion, - Martins, Manuel Rodrigues (2006)
The helical flow resulting from the superposition of mandrel rotation with tubular polymer extrusion is studied. The experiments, carried out under conditions relevant to industrial practice, confirmed a pressure drop reduction upon increasing mandrel rotation and a decrease in torque when increasing the flowrate. An available analytical model was extended to consider the case when the inner wall of the channel is adiabatic and modified to predict torque and pressure drop. The results show a good agreement with experimental data. Information on velocity and viscosity profiles, melt temperature at the outlet, and first and second normal stress differences is also reported. Theoretical and experimental data confirmed unfavourable energy consumption upon mandrel rotation, but at high flowrates the energy consumption is similar to that for conventional static mandrel operation. The model is also used to estimate processing windows favouring the mechanical performance of the extrudate.